POSSIBLE CONTRIBUTION OF DIET AND PHYSICAL INACTIVITY FOR THE PATTERNS OF MORBIDITYAND MORTALITYDYNAMICS, AS REFERRED TO METABOLIC SYNDROME AND CANCER IN AGING (Fiep Bulletin - online, 2013)
(Introduction) Previously we have suggested the important role of physical inactivity and diet in the dynamics of morbidity and mortality due to metabolic syndrome in aging (Goudochnikov, 2005). Besides, our recent study compared the dynamics of relative mortality due to the components of metabolic syndrome and various cancer types in the state of Rio Grande do Sul (RS) during the period 2001-2004 (Goudochnikov, 2007). In the present work this study was amplified, including the data of morbidity of RS, as well the data of morbidity and mortality for another two states, Santa Catarina and Paraná that belong also to Southern region of Brazil. (Methodology) The data for every state were obtained from the database DataSus. The data for each age group and for both sexes were calculated in the form of the percentage of total annual morbidity or mortality in all age groups for each disease, with posterior calculation of the values of arithmetic mean and standard error in the period of 2001-2004. Besides, the fraction of feminine sex was calculated for each age group and each disease, with posterior calculation of the values of arithmetic mean and standard error in the same period of 2001-2004. As for bibliographic analysis, we have evaluated, in amplified mode, Latin-American and world literature, at least in 3 languages and 4 databases, stressing the importance of diet and physical inactivity for the predisposition to various cancer types. (Results) Only some cancer types presented the patterns of age-dependent dynamics of morbidity and mortality, similar to patterns of dynamics of the components of metabolic syndrome. Besides, essential age-related sex differences were observed for some cancer types. The study has not revealed notable differences between the data of the states evaluated. The amplified bibliographic analysis confirmed that, in general, the predisposition to metabolic syndrome amd cancer can have the contribution of diet and physical inactivity. (Conclusion) The results obtained suggest that patterns of the dynamics of morbidity and mortality due to cancer cannot be explained by the unique scheme of aging. On the other hand, it seems that hypocaloric diet and moderate physical activity are able to partially modify the patterns of augmenting morbidity and mortality in aging, causing their translocation to more advanced age groups.
Keywords: cancer; diet; physical inactivity